1996
DOI: 10.1002/(sici)1097-0134(199612)26:4<377::aid-prot2>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence for preexisting T- and R-state insulin hexamer conformations

Abstract: The insulin hexamer is an allosteric protein exhibiting both positive and negative cooperative homotropic interactions and positive cooperative heterotropic interactions (C. R. Bloom et al., J. Mol. Biol. 245, 324-330, 1995). In this study, detailed spectroscopic analyses of the UV/Vis absorbance spectra of the Co(II)-substituted human insulin hexamer and the 1H NMR spectra of the Zn(II)-substituted hexamer have been carried out under a variety of ligation conditions to test the applicability of the sequential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 30 publications
4
42
0
Order By: Relevance
“…The dynamics of 3N4H binding were examined by analysis of the line widths of the 1 H NMR signals for the free and bound species. When 3N4H is present in solutions of the Zn 2+ -R 6 insulin hexamer, two sets of ligand resonances appear in the 1 H NMR spectrum (Choi et al 1996). The resonances of the first set equal those known from the ligand spectrum, whereas the other set represents the ligand bound to the insulin hexamer.…”
Section: Spectroscopic and Kinetic Characterization Of 3n4h Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of 3N4H binding were examined by analysis of the line widths of the 1 H NMR signals for the free and bound species. When 3N4H is present in solutions of the Zn 2+ -R 6 insulin hexamer, two sets of ligand resonances appear in the 1 H NMR spectrum (Choi et al 1996). The resonances of the first set equal those known from the ligand spectrum, whereas the other set represents the ligand bound to the insulin hexamer.…”
Section: Spectroscopic and Kinetic Characterization Of 3n4h Bindingmentioning
confidence: 99%
“…1). This tunnel and the His B10 Zn(II) ion form the anion binding site Brader et al , 1997Choi et al 1993Choi et al , 1996Brzovic et al 1994;Bloom et al 1995Bloom et al , 1997aBloom et al ,b, 1998Huang et al 1997). Two detailed studies of the structure of the Zn 2+ -R 6 hexamer in solution via NMR have been reported (Jacoby et al 1996;Chang et al 1997).…”
mentioning
confidence: 99%
“…Comparison of the observed NMR spectrum with simulated spectra calculated on the basis of the crystallographic protomers reveals that the engineered monomer, although T-like in secondary structure, in part exhibits nuclear Overhauser enhancements (NOEs) between core side chains more consistent with the R-state. These observations support the view that the conformational repertoire of an insulin monomer spans the range of diverse crystal forms (29). The crystal structure of allo-Ile A2 -insulin further demonstrates that the nonstandard substitution does not perturb the surface of the protein, including side chains involved in self-association (9) and/or proposed to contact the insulin receptor (9,25,30,31).…”
mentioning
confidence: 99%
“…12 Since the binding pockets for phenolic ligands are only present in the R form, a ligand independent dynamic equilibrium must form between T and R state before ligand binding. 19 Ligand binding traps the R state and shifts the equilibrium and thus the population probability towards the R state. In addition to formation of hydrophobic binding pockets the conformational changes alter the divalent cation coordination of the three His B10 for each individual trimer.…”
Section: Introductionmentioning
confidence: 99%
“…The conformational state is traditionally analysed with UV absorbing probes having a distinct binding affinity to the T 6 and R 6 state, 5,[7][8][9]19,27,28 or by near UV circular dichroism (CD) monitoring the tertiary conformational state of insulin. 3,8,10,28,29 Both techniques have several drawbacks with respect to pharmaceutical formulations including low compatibility with excipients, the need for relatively well defined conditions, and they are only applicable in solution.…”
Section: Introductionmentioning
confidence: 99%